Boosting DNA Recognition Sensitivity of Graphene Nanogaps through Nitrogen Edge Functionalization - Amorim, Rodrigo G.; Rocha, Alexandre R. [UNESP]; Scheicher, Ralph H. (American Chemical Society (ACS), 2016)
One of the challenges for next generation DNA sequencing is to have a robust, stable, and reproducible nanodevice. In this work, we propose how to improve the sensing of DNA nucleobase using functionalized graphene nanogap as a solid state device. Two types of edge functionalization, namely, either hydrogen or nitrogen, were considered. We showed that, independent of species involved in the edge passivation, the highest-to-lowest order of the nucleobase transmissions is not altered, but the intensity is affected by several orders of magnitude. Our results show that nitrogen edge tends to p-dope graphene, and most importantly, it contributes with resonance states close to the Fermi level, which can be associated with the increased conductance. Finally, the translocation process of nucleobases passing through the nanogap was also investigated by varying their position from a certain height (from +3 to -3 Å) with respect to the graphene sheet to show that nitrogen-terminated sheets have enhanced sensitivity, as moving the nucleobase by approximately 1 Å reduces the conductance by up to 3 orders of magnitude.